KEMAMPUAN DAN KONDISI KOMUNIKASI SOSIALISASI PADA ANAK PENYANDANG DIFABEL TUNAWICARA - Ahmad Gholib Muzakki; Arzia Pratiwi; Fitriya Nur Kumala (Universitas Negeri Surabaya, 2022)
The purpose of the study to describe the ability to communicate on the socialization of homeless children also describes the shape and manner of communication on homeless children and the impact of communication capability on homeless children in communities the research method used is qualitative method with the data-collection technique of library studies. Research data of literature produced by articles and journals related to the title of the study. The approach used is a qualitative approach with the data-collection of data techniques. The data analysis technique on this study is a qualitative technique using miles and huberman model analysis beginning with data gathering, data reduction, data presentation, and finally a deduction. According to the study, homeless children generally have delays in interaction or socialization. This is because children lack the ability to communicate that triggers depression. So children are less able to interact with their surroundings, causing a lack of confidence. A confident child will be able to blend into his environment, even though he has limitations in his body. If he has good self-confidence will surely get a place and be accepted in the communities around him. Keywords: speech impaired, communications, socialization.